A code for 3D calculations of the output characteristics for a single-cell thermionic fuel element of thermionic nuclear power plants for different applications - Polous, M.A.; Solovyev, D.I. V.I. Yarygin; Yarygin, V.I. (My University, 2017)
R&D has been conducted by a cooperation of Rosatom State Corporation’s enterprises to build a line of autonomous small nuclear power plants (SNPP) of up to 1 MW el to support government programs for the development of Russia’s Arctic region. In terms of heat and electricity supplies in an installed electric power range of 10 to 100 kW el , the most attractive solution is offered by highly autonomous, compact and easy-to-maintain SNPPs with an in-core thermionic system. The key component of a thermionic NPP is a thermionic fuel element (TFE), which structurally integrates fuel and electrogenerating elements. Experimental studies and tests of thermionic plants are complex and expensive, so emphasis in the design of TNPPs is placed on mathematical simulation of physical processes taking place in the TFE. The paper considers the results of a 3D numerical simulation for the thermal and electrical characteristics of a single-cell TFE for a TNPP as part of one of the feasible SNPP designs, based on the procedure developed using COMSOL Multiphysics, an advanced software platform, and called by the authors COMSOL-EGK-SC. Initial data have been formulated to calculate a single-cell TFE, stages are described for the TFE mathematical model development in the COMSOL-EGK-SC software environment, and numerical calculation results for the thermal and electrical performance based on experimental data on the current–voltage characteristics (CVC) of a thermionic converter (TC) and the results of a neutronic calculation for the possible structure of the TNPP core as part of an SNPP are presented. Copyright © 2017, National Research Nuclear University MEPhI (Moscow Engineering Physics Institute). Production and hosting by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.
Full text
Keywords: Thermionic NPP; Single-cell thermionic fuel element; Finite element analysis; 3D numerical simulation.